STRATEGI PENGEMBANGAN EKONOMI KREATIF PEREMPUAN PENENUN DESA ENSAID PANJANG KECAMATAN KELAM PERMAI KABUPATEN SINTANG - Dessy Triana Relita; Yulia Suriyanti; Emilia Dewiwati Pelipa; Anna Marganingsih (STKIP Persada Khatulistiwa Sintang, 2022)
One of the creative economies undertaken by women is ‘Tenun Ikat’ traditional handwoven industry. Unfortunately, in Indonesia's industrial development, the handwoven sector is still not capable of being one of the state revenue promised the government's attention. The study aims to determine how the creative economy develops for women's traditional handwoven sector in the village Ensaid Panjang. The study used a qualitative approach. The tool to collect the data used interviews, observation, and documentation. All samples are women. Using a technique subject chosen purposive sampling. To analyse the data used descriptive quantitative research. The study shows that all women are able to develop their small business enterprises in the handwoven sector. It can be seen from the creative endeavour that the women can make new motives in their traditional handwoven, and they also can market it even though some women still cannot use social media to market their products. The government and the coop also assist them in developing their small business by P2Emas program and Koperasi JMM as the coop, which will help them sell the ‘Tenun Ikat’ traditional handwoven.